2023
DOI: 10.1101/2023.07.11.548608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beyond the (geometric) mean: stochastic models undermine deterministic predictions of bet hedger evolution

Maya Weissman,
Yevgeniy Raynes,
Daniel Weinreich

Abstract: Bet hedging is a ubiquitous strategy for risk reduction in the face of unpredictable environmental change where a lineage lowers its variance in fitness across environments at the expense of also lowering its arithmetic mean fitness. Previously, deterministic research has quantified this trade-off using geometric mean fitness (GMF), and has found that bet hedging is expected to evolve if and only if it has a higher GMF than the wild-type. We introduce a novel stochastic framework that leverages both individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Given the low relative fitness of the chasmogamous flower morphs, empirical studies of dimorphic cleistogamy have been unable to show that the strategy increases geometric mean fitness relative to complete cleistogamy (Oakley et al [2007]). Interestingly, recent theoretical work has found that bet hedging strategies can be more adaptive than geometric mean fitness predicts (Weissman et al [2024], Zhou and Xue [2022]). In Weissman et al [2024], we demonstrated that bet hedging can be beneficial at sufficiently large population sizes, even when the geometric mean fitness of the bet hedger is less than that of a resident wild-type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the low relative fitness of the chasmogamous flower morphs, empirical studies of dimorphic cleistogamy have been unable to show that the strategy increases geometric mean fitness relative to complete cleistogamy (Oakley et al [2007]). Interestingly, recent theoretical work has found that bet hedging strategies can be more adaptive than geometric mean fitness predicts (Weissman et al [2024], Zhou and Xue [2022]). In Weissman et al [2024], we demonstrated that bet hedging can be beneficial at sufficiently large population sizes, even when the geometric mean fitness of the bet hedger is less than that of a resident wild-type.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent theoretical work has found that bet hedging strategies can be more adaptive than geometric mean fitness predicts (Weissman et al [2024], Zhou and Xue [2022]). In Weissman et al [2024], we demonstrated that bet hedging can be beneficial at sufficiently large population sizes, even when the geometric mean fitness of the bet hedger is less than that of a resident wild-type. This suggests that dimorphic cleistogamy may be adaptive, even if it causes a decrease in geometric mean fitness relative to complete cleistogamy.…”
Section: Discussionmentioning
confidence: 99%